Weighing the evidence of low glycemic index dietary intervention for the management of gestational diabetes mellitus: an Asian perspective - Mohd Yusof, Barakatun Nisak; Firouzi, Somayyeh; Mohd Shariff, Zalilah; Mustafa, Norlaila; Mohamed Ismail, Nor Azlin; Kamaruddin, Nor Azmi (Informa Healthcare, 2014)
This review aims to evaluate the effectiveness of low glycemic index (GI) dietary intervention for the treatment of gestational diabetes mellitus (GDM), specifically from the Asian perspective. A systematic review of the literature using multiple databases without time restriction was conducted. Three studies were retrieved based upon a priori inclusion criteria. While there was a trend towards improvement, no significant differences were observed in overall glycemic control and pregnancy outcomes in GDM women. However, a tendency for lower birth weight and birth centile if the intervention began earlier was noted. Low GI diets were well accepted and had identical macro-micronutrient compositions as the control diets. However, due to genetic, environment and especially food pattern discrepancies between Western countries and Asians, these results may not be contributed to Asian context. Clearly, there are limited studies focusing on the effect of low GI dietary intervention in women with GDM, particularly in Asia.